Solomon Stephens indenture for a military bounty land grant - Stephens, Solomon
Indenture for a military bounty land grant in Illinois territory registered at the U.S. General Land Office, Washington, D.C., with an attachment signed by U.S. Secretary of State John Quincy Adams.
U.S. Army private.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Adams, John Quincy, -- 1767-1848.; United States. -- General Land Office; Bounties, Military -- Illinois; Deeds -- Illinois; Land grants -- Illinois; Public lands -- Illinois; Soldiers